2023
DOI: 10.1126/sciadv.adi4517
|View full text |Cite
|
Sign up to set email alerts
|

Origin and functional diversification of PAS domain, a ubiquitous intracellular sensor

Jiawei Xing,
Vadim M. Gumerov,
Igor B. Zhulin

Abstract: Signal perception is a key function in regulating biological activities and adapting to changing environments. Per-Arnt-Sim (PAS) domains are ubiquitous sensors found in diverse receptors in bacteria, archaea, and eukaryotes, but their origins, distribution across the tree of life, and extent of their functional diversity are not fully characterized. Here, we show that using sequence conservation and structural information, it is possible to propose specific and potential functions for a large portion of nearl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 159 publications
0
7
0
Order By: Relevance
“…Although hundreds of different sensor domains have evolved (2,6) and new ones are regularly being discovered (7,8), only a few of them are ubiquitous. For example, PAS domains comprise one of the largest superfamilies of intracellular sensors (9), whereas homologous Cache domains form one of the largest superfamilies of extracellular sensors (10).…”
Section: Introductionmentioning
confidence: 99%
“…Although hundreds of different sensor domains have evolved (2,6) and new ones are regularly being discovered (7,8), only a few of them are ubiquitous. For example, PAS domains comprise one of the largest superfamilies of intracellular sensors (9), whereas homologous Cache domains form one of the largest superfamilies of extracellular sensors (10).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the PAS domains of KCNH channels harbor binding sites for structurally distinct ligands, including tricyclic drugs, such as chlorpromazine and imipramine [25;26] in EAG1 channels, heme [46] in ERG3 channels and undecylenic acid [24] in EAG1 channels. Considering the evolutionary function of PAS domains as ligand-binding modules and their suitability for drug targeting [30], identification and design of additional KCNH PAS domain ligands is imminent. This raises the importance of mechanistic understanding of KCNH channel modulation by the PAS domain ligands.…”
Section: Discussionmentioning
confidence: 99%
“…How binding of the small molecule ligands to the intracellularly located PAS domains can affect current flow through the centrally located pore of the channel is not known. Although, KCNH channels are the only ion channels containing PAS domains, the PAS domain fold is quite common in other proteins and is frequently targeted for drug design [27][28][29][30]. It is highly likely that many more EAG1 PAS domain small molecule binders will be identified in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we propose that changes to the intracellular environment in phenazine-deficient cells or cells with low Crc activity may stimulate PhoR activity through its PAS domain. Future work into the mechanisms of the PhoR PAS domain would also be beneficial for understanding similar kinases in P. aeruginosa and other organisms as PAS domains are abundant but remain poorly understood ( 103 ). Understanding LasR– P. aeruginosa virulence in physiologically relevant conditions is critical as LasR– isolates are frequently found in both acute and chronic infections and these findings may be relevant to P. aeruginosa when in settings that do not induce QS regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we propose that changes to the intracellular environment in phenazine-deficient cells or cells with low Crc activity may stimulate PhoR activity through its PAS domain. Future work into the mechanisms of the PhoR PAS domain would also be beneficial for understanding similar kinases in P. aeruginosa and other organisms as PAS domains are abundant but remain poorly understood (103) .…”
Section: Further Work Is Needed To Elucidate the Mechanisms By Which ...mentioning
confidence: 99%